Risk Factors Associated with Newborn Hearing Impairment in the Neonatal ICU of a Tertiary Hospital - Shameem, Md; Saha, Kanu Lal; Uddin, Md Belal; Jahan, Jesmin; Rahman, Md Khalilur; Islam, KM Saiful (TAJ: Journal of Teachers Association, 2023)
Introduction: Hearing impairment has a devastating, detrimental, and adverse impact on the development of the newborn. Unfortunately, this hidden disability remains undetected for many newborns until it is too late to prevent undesirable and often irreversible damage. It has long been recognized that undiagnosed hearing loss, even a mild loss at birth, can negatively affect speech and language development, Resulting in poor academic achievement and social-emotional development. According to WHO 2009, newborns in the NICU are 10-20 times at higher risk of developing hearing loss. The risk factors associated with newborn hearing impairment vary from country to country and even within countries. There has been a paucity of studies on this topic from Bangladesh. This study was done to identify the risk factors associated with newborn hearing impairment in the study place. The objective of the study: To identify risk factors associated with newborn hearing impairment in the study group. Methodology: A prospective observational study was conducted in the department of neonatology, BSMMU. After taking consent from the parents/guardians, a thorough history of these newborns, including particulars of the neonates, family history of hearing loss, treatment history, antenatal, natal, and postnatal history, was recorded in a data collection form. Newborn admitted to the NICU during the study period was the study population. The newborn who meet the inclusion criteria was screened with Transient Evoked Otoacoustic Emissions (TEOAE) close to discharge from the NICU or before one month of age. A second screen was done with TEOAE again after one month of 1st screen but prior to 3 months of postnatal age if referred in 1st screen. Diagnostic Auditory Brain stem Response (ABR) was made to confirm the hearing impairment, and it was done prior to 3 months of postnatal age if referred in both the 1st and 2nd screens. Data were analyzed by statistical package for social sciences (SPSS) version 20. Results: 426 valid recordings from 493 newborns admitted in the NICU enrolled consecutively constitute the basis of this study. 14 newborns were found to have hearing impairment among 426 newborns. APGAR ≤ 6 at 5 minutes (odds ratio 20.34, p-value 0.01), TORCH infection (odds ratio 0.64, p-value 0.01), IUGR odds ratio 8.92, p-value 0.02) were independent significant risk factors for hearing impairment. Conclusion: APGAR ≤ 6 at 5 minutes, TORCH infection, and IUGR are independent significant risk factors for newborn hearing impairment. Newborns in NICU with these risk factors should have mandatory audiological evaluation. TAJ 2022; 35: No-2: 59-65